2015
DOI: 10.1002/app.42217
|View full text |Cite
|
Sign up to set email alerts
|

On the use of ball milling to develop poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate)‐graphene nanocomposites (II)—Mechanical, barrier, and electrical properties

Abstract: In this work, poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) nanocomposites containing functionalized graphene sheets (FGS) were prepared by means of high‐energy ball milling. The crystalline structure, oxygen barrier, mechanical and electrical properties, and biodegradability of the developed nanocomposites were analyzed and correlated with the amount of FGS incorporated and with their morphology, which was reported in a previous study. Addition of FGS into the PHBV matrix did not affect the crystal mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…While the relative intensity ratio of the neat PHBV matrix was 1.42, this value increased up to 4.58 for the OSBN nanocomposites and 6.72 for OSFBN nanocomposites. The increase in the relative ratio implies that crystal growing was promoted in (020) crystal plane as reported [ 38 , 39 ].…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…While the relative intensity ratio of the neat PHBV matrix was 1.42, this value increased up to 4.58 for the OSBN nanocomposites and 6.72 for OSFBN nanocomposites. The increase in the relative ratio implies that crystal growing was promoted in (020) crystal plane as reported [ 38 , 39 ].…”
Section: Resultssupporting
confidence: 55%
“…While the intensity of (020) peak of PHBV increases, the intensity of (110) peak of PHBV becomes lower with boron nitride addition. The increase of (020) peak of PHBV could be related to the crystallite lamella size of polymer and indicated that crystallization is promoted by boron nitride addition [ 38 ]. The decrease of (110) peak of PHBV indicates the restricted crystal growth in (110) plane.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Ambrosio-Martín et al ( 2015a , b ) prepared novel nanocomposites based on PHBV and functionalized graphene nanosheets (FGS) by means of mechano-physic ball milling method. Morphological characterization evidenced proper nanofiller dispersion into the matrix, whereas DSC analysis evidenced an increased crystallinity of the polymer.…”
Section: Chemical and Physical Strategies To Improve Post-smentioning
confidence: 99%
“…Thermal stability tests revealed that FGS affected the mechanism of oxidative thermal degradation while they did not influence the thermal degradation by pyrolysis. The authors highlighted the positive influence of the homogeneous dispersion of FGS nanofiller within the polymeric matrix, for both the mechanical reinforcing effect of FGS and also gas barrier enhancement (Ambrosio-Martín et al, 2015a , b ).…”
Section: Chemical and Physical Strategies To Improve Post-smentioning
confidence: 99%
“…In addition to the above findings, the addition of Gr to biodegradable polymers has been applied in electrical materials, fire retardant materials, sensors and catalysts, etc. [123,124,126,127]. However, the number of studies in these fields is relatively few, and further study on the enhancement of relevant properties is needed.…”
Section: Applications Of Graphene/polymer Composite Materialsmentioning
confidence: 99%